Ambient gold-catalyzed O-vinylation of cyclic 1,3-diketone: A vinyl ether synthesis - Xi, Yumeng; Dong, Boliang; Shi, Xiaodong (Beilstein Journal of Organic Chemistry, 2013)
Gold-catalyzed O-vinylation of cyclic 1,3-diketones has been achieved for the first time, which provides direct access to various vinyl ethers. A catalytic amount of copper triflate was identified as the significant additive in promoting this transformation. Both aromatic and aliphatic alkynes are suitable substrates with good to excellent yields.
Keywords: alkyne; copper salt; diketone; gold catalysis; vinyl ether

Modern Gold Catalyzed Synthesis - Hashmi, A. S. K.; Toste, F. D. (Wiley-VCH, 2012)

(untitled) - Gorin, D. J.; Sherry, B. D.; Toste, F. D. (Chem. Rev., 2008)

(untitled) - Arcadi, A. (Chem. Rev., 2008)

(untitled) - Jiménez-Núñez, E. S.; Echavarren, A. M. (Chem. Rev., 2008)

(untitled) - Hashmi, A. S. K. (Chem. Rev., 2007)

(untitled) - Fürstner, A.; Davies, P. W. (Angew. Chem., Int. Ed., 2007)

(untitled) - Jiménez-Núñez, E.; Echavarren, A. M. (Chem. Commun., 2007)

(untitled) - Hashmi, A. S. K.; Hutchings, G. J. (Angew. Chem., Int. Ed., 2006)

(untitled) - Zhang, L.; Sun, J.; Kozmin, S. A. (Adv. Synth. Catal., 2006)

(untitled) - Hashmi, A. S. K.; Rudolph, M. (Chem. Soc. Rev., 2008)

(untitled) - Rudolph, M.; Hashmi, A. S. K. (Chem. Soc. Rev., 2012)

(untitled) - Teles, J. H.; Brode, S.; Chabanas, M. (Angew. Chem., Int. Ed., 1998)

(untitled) - Mizushima, E.; Sato, K.; Hayashi, T.; Tanaka, M. (Angew. Chem., Int. Ed., 2002)

(untitled) - Leyva, A.; Corma, A. (J. Org. Chem., 2009)

(untitled) - Marion, N.; Ramón, R. S.; Nolan, S. P. (J. Am. Chem. Soc., 2009)

(untitled) - Krauter, C. M.; Hashmi, A. S. K.; Pernpointner, M. (ChemCatChem, 2010)

(untitled) - Corma, A.; Ruiz, V. R.; Leyva-Pérez, A.; Sabater, M. J. (Adv. Synth. Catal., 2010)

(untitled) - Winternheimer, D. J.; Shade, R. E.; Merlic, C. A. (Synthesis, 2010)

(untitled) - Chary, B. C.; Kim, S. (J. Org. Chem., 2010)

(untitled) - Luo, T.; Dai, M.; Zheng, S.-L.; Schreiber, S. L. (Org. Lett., 2011)

(untitled) - Kuram, M. R.; Bhanuchandra, M.; Sahoo, A. K. (J. Org. Chem., 2010)

(untitled) - Oonishi, Y.; Gómez-Suárez, A.; Martin, A. R.; Nolan, S. P. (Angew. Chem., Int. Ed., 2013)

(untitled) - Lee, P. H.; Kim, S.; Park, A.; Chary, B. C.; Kim, S. (Angew. Chem., Int. Ed., 2010)

(untitled) - Nun, P.; Egbert, J. D.; Oliva-Madrid, M.-J.; Nolan, S. P. (Chem.–Eur. J., 2012)

(untitled) - Mo, J.; Kang, D.; Eom, D.; Kim, S. H.; Lee, P. H. (Org. Lett., 2013)

(untitled) - Duan, H.; Sengupta, S.; Petersen, J. L.; Akhmedov, N. G.; Shi, X. (J. Am. Chem. Soc., 2009)

(untitled) - Chen, Y.; Yan, W.; Akhmedov, N. G.; Shi, X. (Org. Lett., 2010)

(untitled) - Wang, D.; Ye, X.; Shi, X. (Org. Lett., 2010)

(untitled) - Wang, D.; Gautam, L. N. S.; Bollinger, C.; Harris, A.; Li, M.; Shi, X. (Org. Lett., 2011)

(untitled) - Wang, Q.; Aparaj, S.; Akhmedov, N. G.; Petersen, J. L.; Shi, X. (Org. Lett., 2012)

(untitled) - Guérinot, A.; Fang, W.; Sircoglou, M.; Bour, C.; Bezzenine-Lafollée, S.; Gandon, V. (Angew. Chem., Int. Ed., 2013)